A Social History of Iranian Cinema, Volume 2 : The Industrializing Years, 1941-1978 - Naficy, Hamid (Book collections on Project MUSE., 2011)
"Hamid Naficy is one of the world's leading authorities on Iranian film, and A Social History of Iranian Cinema is his magnum opus. Covering the late nineteenth century to the early twenty-first and addressing documentaries, popular genres, and art films, it explains Iran's peculiar cinematic production modes, as well as the role of cinema and media in shaping modernity and a modern national identity in Iran. This comprehensive social history unfolds across four volumes, each of which can be appreciated on its own"--Publisher's description.